Analisis Penyebab Rendahnya Kedisiplinan Pegawai Pada Unit Pelaksana Teknis Daerah (UPTD) Kesatuan Pengelolaan Hutan Produksi (KPHP) Dharmasraya Dinas Kehutanan Provinsi Sumatera Barat Menggunakan Grounded Theory - Fetri Nelfa; Jerry Heikal (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
Employee discipline is an important factor in achieving organizational performance. Disciplined employees will comply with regulations, complete tasks on time, and show a professional attitude at work. Low employee discipline can have a negative impact on organizational performance, such as decreasing productivity, service quality and organizational image. Discipline is something that can be used as a benchmark to determine whether the functions of human resource management or leadership as a whole have been carried out well or not. This research aims to determine the factors that contribute to the low level of employee discipline at the UPTD KPHP Dharmasraya Forest Service of West Sumatra Province. The research method used is qualitative research with a Grounded Theory approach. The results of this research state that. factors that contribute to the low level of employee discipline at the UPTD KPHP Dharmasraya West Sumatra Province Forestry Service, ethical awareness, socio-economic impacts, reward and punishment systems, HRD policies and mental health.